Application of radiogenic isotopes in Geosciences: Overview and perspectives - Tessalina, Svetlana; Jourdan, Fred; Nunes, L.; Kennedy, A.; Denyszyn, S.; Puchtel, I.; Touboul, M.; Creaser, R.; Boyet, M.; Belousova, E.; Trinquier, A. (Royal Society of Chemistry, 2015)
Wider use of radiogenic isotopes in geosciences has been enabled by developments in mass spectrometry at the beginning of the 21st century. Nowadays, radiogenic isotope geochemistry forms an integrated part of geosciences in a range of applications, starting from formation of planetary systems, genesis, and the evolution of Earth's lithosphere and associated mineral and oil deposits, as well as environmental tracers. Two primary types of information are available from radiogenic isotopes studies: age determination and isotopic source tracing. In this chapter, the range of isotope systematics currently used in geosciences and their applications are reviewed, together with progress in analytical technologies. The chapter brings together internationally recognised researchers who have been at the forefront of analytical technologies in the field of geochemistry of radiogenic isotopes.